Pengaruh Ekstrak Daun Ceremai (Phyllanthus acidus [L.] Skeels) terhadap Kadar IgE pada Mencit Model Alergi - Subijanto, AA; HP, Diding (Jurnal Kedokteran YARSI, 2008)
It was reported in previous studies that pharmacological activities were identified in various compounds extracted from Phyllanthus Acidus (PA) such as anti-inflammatory, antilipoxigenase, anti-allergic and cyclooxigenase inhibitor. It is also acknowledged that Ig E serum level is normally low and usually increase in allergic conditions. This study was aimed to determine the effect of PA leaf extract on Ig E level in mice model of allergic asthma. Male Balb/C mice were sensitized and challenged intraperitoneally (i.p) with ovalbumin(OVA). Mice were immunized i.p. on days 4 and 20 with 2.5 mg of OVA adsorbed to 7.75ml of Aluminum hydroxide gel. OVA challenges (10 mg in l0 ml of PBS) were administered aerosolly on days 26, 29, 32, 39 and 46, with mice being sacrificed on day 47. Ig E level in serum was determined using ELISA kits (Alpha Diagnostic, USA) according to the manufacturer's instructions. A one-way analysis of variance (ANOVA) with LSD post hoc analysis was used to determine significant differences. Results were expressed as mean + SEM, and values of p < 0.05 were considered statistically significant. The results showed that Ig E level in the negative control group was 50.13+33.40 ng/ml, PA leaf extract was 51.17+26.15 ng/ml, and positive control group was 48.97+33.50 ng/ml while OVA group was 152.89+58.00 ng/ml (p >0.05). It was concluded that PA leaf extract could minimize Ig E level, not significantly different with 3rd generation of antihistamine.